An Analysis of Word Formation Process in I Am Malala Novel by Malala Yousafzai - Sinulingga, Desi Rahma Yuni Br.; Deliana, Deliana (Politeknik Harapan Bangsa Surakarta, 2022)
The aim of this research is to find the used of the types and the most dominant types of word formation process in I Am Malala novel by Malala Yousafzai. This is a qualitative descriptive research by Miles and Huberman (2014). The words were analized by using Oâ€™Grady and Guzman (2010) theory. From the analysis, the writer found 12 from 14 word formation types process with the classifying. 33 of Borrowing (3,09%), 130 of Compounding (12,17%), 4 of Reduplication (0,37%), 318 of Inflection (29,78%), 34 of Suppletion (3,18%), 75 of Internal Change (7,02%), 5 of Coinage (0,47%), 5 ofÂ Onomatopoeia (0,47%), 53 of Acronyms (4,97%), 5 of Clipping (0,47%) ,14 of Back Formation (1,31%), and 392 of Derivation (36,70%). Also found the most dominant type is Derivation. It has 36,70% of the total term. The total of Derivation is 392 words from total 1.068 words.